Maelwael Johan Maelwael, Nijmegen - Paris - Dijon : art around 1400 - Roelofs, Pieter 1972-; Dückers, Rob 1972-; Ravaud, Élisabeth; Schmidt, Victor Michael 1957-; Scholten, Frits 1959-; Thiébaut, Dominique; Ubl, Matthias (Rijksmuseum, 2017)
Johan Maelwael (1365/70-1415), internationally known as Jean Malouel, was one of the most important West European artists of the late Middle Ages. He grew up in Nijmegen as a scion of a family of successful heraldic painters and later became the court painter of the Dukes of Burgundy. This great innovator in painting created his multifaceted oeuvre nearly a century before Hieronymus Bosch. His painting is characterized by elegantly sophisticated figures, a high degree of realism and a bright colour palette with deep shades of blue, red and gold. This publication describes Maelwael's life, his versatile work and his place in history. The paintings of Maelwael, who is rather unknown in the Netherlands, are displayed together with a wealth of unique medieval art treasures, paintings, precious metalwork, sculptures, drawings and manuscripts including richly decorated manuscripts by his legendary cousins, the Limbourg brothers, and lifelike portraits by his contemporary, Claes Sluter